Role playing in human evolution: from life to art, and everything in between - Brown, Steven (Frontiers in Psychology, 2025)
Role playing is a central, but underappreciated, process in human evolution. It is a feature not only of the theatrical arts, but of everyday social interactions. While some role playing is limited to enacting various personas of the self (e.g., wife, accountant, mother), others involve an impersonation of people. The most basic form of impersonation is proto-acting, which refers to a transient engagement in character portrayal, such as when we quote a friend during a conversation. During proto-acting, we “act as” some other person. However, there are other means of acting in a similar manner to another person in which we do not impersonate them, but merely emulate their behavior. This might happen when we learn a motor skill from a teacher or conform to the consumer choices of the masses. This follower-based process of “acting like” is a critically important mechanism in cultural evolution since it leads to social conformity and the homogenization of group behavior. I argue that the evolutionary transition from “acting like” (emulation) to “acting as” (impersonation) occurred via the emergence of pantomime and its narrative depiction of the actions of other people. This was probably the first step toward impersonating someone, leading initially to proto-acting and later to theatrical performance in human cultures. Overall, the study of human evolution needs to give greater consideration to role playing and its diverse manifestations in life and art.